SLANG DALAM FILM SUICIDE SQUAD KARYA DAVID AYER - PADATI, ANENDA PUTRI; RATTU, JULTJE A.J.; SENDUK, ARTER J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTThis research is entitledÂ â€œSlang in theÂ film Suicide Squad by David Ayerâ€. This research aims are to identify the slangs foundÂ in the Film Suicide Squad, and analyze and describe their forms and meanings.The slangs data were collected from the film script which consists of 41 pages. The writer also uses some theory that related to slang language and definition of slang the theory used in this research is by Bloomfield and Guth. Theoretically, the writer hopes that this research can give some contributions to the enlargement especially of the sociolinguistics field more especially on slang word.From analysis this research, the writer analysis found six types of slang, they are: abbreviation, facetious mispronunciation, shortened, interjection, figurative, nick name (calling person).Form this research, the result show that are 2 slangs in the abbreviation, 10 slangs in facetious mispronunciation, 11 slangs in shortened, 8 slangs in interjection, 11 slangs in figurative, and 18 slangs in nick name.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keyword: Slang, Film Suicide Squad, Bloomfield and Guthâ€™s theory